Extracellular signal-regulated kinase in the basolateral amygdala is required for reconsolidation of heroin-associated memory - Li, Haoyu; Hu, Ting; Zhang, Yanghui; Zhao, Zijin; Liu, Qing; Chen, Zihua; Chen, Si (Frontiers in Molecular Neuroscience, 2022)
Reconsolidation of heroin-associated memory is an independent memory process that occurs following retrieval, which is essential for the sustained capacity of an associative drug stimulus to precipitate heroin-seeking. Extracellular signal-regulated kinase (ERK) in the basolateral amygdala (BLA) mediates the reconsolidation of drug memory. In the present study, we utilized a rat model of drug craving and relapse to verify the hypothesis that the reconsolidation of heroin-associated memory requires ERK in an instrumental heroin-seeking behavior, focusing on the BLA brain region, which is crucial for synaptic plasticity and memory processes. We found that bilateral intra-BLA infusions of U0126 (1 μg/0.5 μl), an ERK inhibitor, immediately after retrieving heroin-associated memory significantly reduced cue-induced and drug-induced reinstatement and spontaneous recovery of heroin-seeking compared to the vehicle. Furthermore, this inhibitory effect was related to the characteristic of reconsolidation. Conversely, no effect was observed on the heroin-seeking behavior when the intra-BLA infusion of U0126 was administered 6 h after the heroin-associated memory retrieval or without memory retrieval. Together, these data suggest that disrupting the reconsolidation of heroin-associated memory via an ERK inhibitor may serve as a promising option for treating relapse in opiate addicts.